(untitled) (Journal of Pharmaceutical Negative Results, 2022)
AIMS AND OBJECTIVES: Splenic abscess is an uncommon entity with significant morbidity and mortality. The aim of this study was to review our experience with splenic abscesses, with respect to the relevant aspects of splenic abscesses, causes and management outcomes. MATERIALS AND METHODS: We had reviewed 10 patients with splenic abscesses and who were treated at our hospital from May 2019 to June 2021. RESULTS: The mean age of the patients was 48.12±6.76 years and majority of patients were males (70%). The most prevalent symptom was abdominal pain in 6 patients (60%) followed by sensation of chills in 4 patients (40%). Splenomegaly was seen in 70% of the patients. The median duration from symptom onset until establishment of a diagnosis was 22 days. Streptococcus viridians was the most common pathogen (40%), followed by Klebsiella pneumoniae (20%). The inpatient mortality rate and the previous 90 days was 20%. All the patients with Klebsiella pneumoniae showed a single abscess pocket. Two patients (20%) underwent percutaneous drainage, Five (50%) received antibiotic treatment only and 3(33.3%) underwent splenectomy. CONCLUSION: In conclusion, the best therapeutic approach for splenic abscess is still a matter of debate. We agree with the traditional treatment of antibiotics with or without splenectomy. However, based on our experience and the current literature, percutaneous aspiration of splenic abscess can be used as a bridge to surgery for those patients who are critically ill or who have several comorbidities.